RESOURCE APPROACH TO PSYCHOLOGICAL CAPITAL AND HUMAN'S CONSCIOUS SELF-REGULATION - Morosanova, V.I.; Avanesyan, H.M. (Modern Psychology, 2020)
The article is devoted to a resource approach to the study of psychological capital and conscious human self-regulation. Its main provisions were formulated earlier (V.I. Morosanova, 2014, 2017, 2019), and this article aims to reveal the resource nature of these phenomena, which are most important for achieving professional and educational goals. In the context of the problem, the main aspects of the study of psychological capital are analyzed. It is concluded that conscious self-regulation is a metasystem of universal and special resources of a person that allows contributing to the productive aspects of achieving goals, as well as activating the reserves of psychological capital to achieve various vital functions.
Keywords: psychological capital; resource approach; self-recognized self- regulation; educational; professional activity